The Effect Of Relationship Marketing, Food Quality And Service Quality On Customer Satisfaction With Purchase Decisions As Intervening Variables - Selvi Ainul Inayah Dwiyanti; Muchammad Saifuddin (At-tijaroh: Jurnal Ilmu Manajemen dan Bisnis Islam, 2022)
This study aims to know role of purchase decision as a mediating effect between relationship marketing, food quality dan service quality on customer satisfaction, the sampling used 100 respondents. The data was analyzed using Partial Least Square (PLS) which consists of two stages, outer model and the inner model with the help of the SmartPLS program. 3.2 The results show that Relationship Marketing has significant effect on customer satisfaction. Relationship Marketing has significant effect on purchasing decisions. Service Quality has significant effect on customer satisfaction. Purchase decisions have significant effect on customer satisfaction. Relationship Marketing through Purchase Decisions has significant effect on Customer Satisfaction. With the results of this study, it is hoped that it can be used as input and evaluation material to improve food quality and service quality in the hope that Nelongso fried chicken has more value than other restaurants in the minds of consumers.